Digital Marketing Rumah Makan Padang Melalui Instagram Berdasarkan Social Construction of Technology - Dionisius Lesmana; Gabriella Monique Valentina (COMMENTATE: Journal of Communication Management, 2021)
Technology innovation leads to digitalization through the internet encourages the emergence of social media as a trend in Indonesia, such as Instagram. Nowadays, Instagram optimized as a digital marketing communication media as a form of social construction of technology. Present culinary business often found on Instagram, different from conventional business such as Padang Restaurant which already known before digital era. But nowadays, the present Padang Restaurant pops up and they already have an Instagram account such as Wira Padang Restaurant. This research aims to see the social construction of technology process from Padang Restaurant’s Instagram account as a form of social construction of technology and to see its digital marketing process. This research using a qualitative method with case study approach through depth interview. The result shows that Padang Restaurant’s Instagram account as a social construction of technology form goes through negotiation of Instagram’s users and business owner to reciprocally share information, Instagram’s features and services as a business account are satisfying for the relevance social group and Instagram as a business account entering the closure and stabilization form. The broader context seen in the Instagram user’s habit to upload their food on Instagram and it’s been a trend for business owner to create an Instagram account to receive digital recognition. Digital marketing activities on Instagram seen in branding aspect, executed through contents, tone feeds, caption/style of language, hashtag. Completeness aspect seen through Campsite. Instagram’s functionality is user friendly, interactivity seen through the relation that was built, visual communication seen at color identities for brand recall, Instagram ads and publication by influencer, food blogger as the relevant advertisement, community relations maintained through intense, exclusive approach, connectivity with another media social creates virality.